2018
DOI: 10.1002/jso.25170
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes after robot‐assisted versus laparoscopic distal pancreatectomy: Analysis of the National Cancer Database

Abstract: The early national experience with RDP demonstrates similar oncologic outcomes to LDP, with a significantly lower conversion rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 24 publications
2
48
0
2
Order By: Relevance
“…Considering our short follow-up (2 years) and the small sample size, it is not possible to draw strong conclusions in terms of long-term disease-free and overall survival but until now we observed a similar recurrence rate in the laparoscopic versus robotic group (4/20 vs. 4/21) as recently reported by a National Cancer Database involving 704 patients [50].…”
Section: Discussionsupporting
confidence: 66%
“…Considering our short follow-up (2 years) and the small sample size, it is not possible to draw strong conclusions in terms of long-term disease-free and overall survival but until now we observed a similar recurrence rate in the laparoscopic versus robotic group (4/20 vs. 4/21) as recently reported by a National Cancer Database involving 704 patients [50].…”
Section: Discussionsupporting
confidence: 66%
“…This study did not aim to assess the if and what the MIS approach was safe or appropriate. A recent report from the National Cancer Data Base comparing laparoscopic and robotic distal pancreatectomy had similar short‐term outcomes including length of hospital stay and 30‐day readmission rate, as well as similar long‐term oncologic outcomes including overall survival 6 . Rather, our study aimed to review granular data as it pertains to cost with the various operative approaches to distal pancreatectomy.…”
Section: Discussionmentioning
confidence: 98%
“…A recent report from the National Cancer Data Base comparing laparoscopic and robotic distal pancreatectomy had similar short-term outcomes including length of hospital stay and 30-day readmission rate, as well as similar long-term oncologic outcomes including overall survival. 6 Rather, our study aimed to review granular data as it pertains to cost with the various operative approaches to distal pancreatectomy. We were unable to adequately compare the cost of conversion for laparoscopic and robotic procedures due to the low number of converted laparoscopic procedures (n = 3) in our cohort, but it was clear that robotic surgery had the highest operating room costs.…”
Section: Cost Comparisonmentioning
confidence: 99%
“…Another prospective study compared robotic with laparoscopic single-site distal pancreatectomy and found longer operative time for the robotic approach, while postoperative and oncologic outcomes were similar [35]. In contrast, analysis of the US NCDB demonstrated comparable oncologic outcomes, but a higher conversion rate for laparoscopic distal pancreatectomy [36].…”
Section: Laparoscopic Versus Robotic Distal Pancreatectomymentioning
confidence: 99%